75.8k views
3 votes
A recursive rule for an arithmetic sequence is a₁=4;a_n=a_(n−1)−3 .

What is the explicit rule for this sequence?




Enter your answer in the box.


a_n=

User Maribelle
by
6.4k points

1 Answer

1 vote

The explicit formula of the arithmetic sequence:


a_n=a_1+(n-1)d

d - common difference

We have the recursive formula of an arithmetic sequence:


\left\{\begin{array}{ccc}a_1=4\\a_n=a_(n-1)-3\end{array}\right

Therefore we have:


a_1=4,\ d=-3

Substitute:


a_n=4+(n-1)(-3)=4-3n+3=7-3n

Answer: aₙ = 7 - 3n

User Thomas Rosa
by
6.1k points